2007
DOI: 10.1016/j.pain.2006.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Spinal microglia and neuropathic pain in young rats

Abstract: Neuropathic pain behaviour is not observed in neonatal rats and tactile allodynia does not develop in the spared nerve injury (SNI) model until rats are 4 weeks of age at the time of surgery. Since activated spinal microglia are known to play a key role in neuropathic pain, we have investigated whether the microglial response to nerve injury in young rats differs from that in adults. Here we show that dorsal horn microglial activation, visualised with IBA-1 immunostaining, is significantly less in postnatal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 42 publications
9
84
0
Order By: Relevance
“…2006). Because microglial response triggered by nerve injury is not mature before P16 (Moss et al 2007) and synaptogenesis in the PrV occurs mainly in the first postnatal week, we believe the effects of RB-2 and SRMN on synaptogenesis are caused by blocking the activation of astrocytes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2006). Because microglial response triggered by nerve injury is not mature before P16 (Moss et al 2007) and synaptogenesis in the PrV occurs mainly in the first postnatal week, we believe the effects of RB-2 and SRMN on synaptogenesis are caused by blocking the activation of astrocytes.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, astrocytes could be inducing both sprouting and synapse formation. Finally, the consequences of this neonatal reactive synaptogenesis in the adult state are not known but may lead to hypersensitivity of the pathway or neuropathic pain conditions (Moss et al 2007;Okada-Ogawa et al 2009). Pharmacological intervention of astrocyte signaling at various levels offers venues of ameliorating the peripheral nerve injury-induced reactive synaptogenesis in the neonatal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, full thickness skin wounds, and skin incision produce prolonged alterations in sensitivity and in the response to future injury in the absence of any visible persistent peripheral injury. By contrast, allodynia following nerve injury is less apparent in early life (Howard et al, 2005;Moss et al, 2007). These findings are of considerable importance as pain and injury in neonates may have effects on nociceptive processing that differ in mechanism and duration from that experienced by older children and adults.…”
Section: Long-term Consequences Of Early Pain and Injurymentioning
confidence: 95%
“…Work emanating from the laboratory of Professor Maria Fitzgerald at University College, London, focussed on the lack of neuropathic pain in neonates by investigating the involvement of non-neuronal, neuroimmune cells in the maturing spinal cord. Moss et al (2007) demonstrated that although both the glutamate receptor agonist NMDA or the inflammogen lipopolysaccharide could activate resident microglia within the spinal cord of 10-day old rodents, spared nerve injury could not. Furthermore, the intrathecal injection of cultured and ATP-activated (proinflammatory) microglia into the spinal cord of this age group of rats failed to provoke a mechanical allodynia which is seen when the same manipulation is attempted in adults.…”
Section: Neuropathic Pain In Early Life and The Consequences Of Neonamentioning
confidence: 99%